THE ECONOMIC COMPONENTS OF SUSTAINABLE DEVELOPMENT FUNCTION AT THE LEVEL OF THE INDUSTRIALENTERPRISES - Gabriela DOBROTĂ (Fiabilitate şi Durabilitate)
Abstract The activities carried out under industrial enterprises often involves, obtainingfinancial surpluses on the base of excessive use of natural resources and the absence ofenvironmental protection measures. Or, the need to ensure optimal conditions for future generationsrequires the correlation the economic, technological, political and social measures withrequirements of sustainable development. The present research aims at outlining the components ofsustainable development and the identification of indicators that enable sustainable economicdevelopment tool in the industrial entities, specifying factors influence them